Evaluation of the pattern of treatment, level of anticoagulation control, and outcome of treatment with warfarin in patients with non-valvar atrial fibrillation: a record linkage study in a large British population. Issue 4 (16th March 2005) - Jones, M; McEwan, P; Morgan, C Ll; Peters, J R; Goodfellow, J; Currie, C J
Abstract : Objective: To evaluate how well patients with non-valvar atrial fibrillation (NVAF) were maintained within the recommended international normalised ratio (INR) target of 2.0–3.0 and to explore the relation between achieved INR control and clinical outcomes. Design: Record linkage study of routine activity records and INR measurements. Setting: Cardiff and the Vale of Glamorgan, South Wales, UK. Participants: 2223 patients with NVAF, no history of heart valve replacement, and with at least five INR measurements. Main outcome measures: Mortality, ischaemic stroke, all thromboembolic events, bleeding events, hospitalisation, and patterns of INR monitoring. Results: Patients treated with warfarin were outside the INR target range 32.1% of the time, with 15.4% INR values > 3.0 and 16.7% INR values < 2.0. However, the quartile with worst control spent 71.6% of their time out of target range compared with only 16.3% out of range in the best controlled quartile. The median period between INR tests was 16 days. Time spent outside the target range decreased as the duration of INR monitoring increased, from 52% in the first three months of monitoring to 30% after two years. A multivariate logistic regression model showed that a 10% increase in time out of range was associated with an increased risk of mortality (odds ratio (OR) 1.29, p < 0.001) and of an ischaemic stroke (OR 1.10, p  =  0.006) and other thromboembolic events (OR 1.12, p < 0.001). The rate of hospitalisation was higher when INR was outside the target range. Conclusions: Suboptimal anticoagulation was associated with poor clinical outcomes, even in a well controlled population. However, good control was difficult to achieve and maintain. New measures are needed to improve maintenance anticoagulation in patients with NVAF.